Early Physiotherapy Intervention Following Corrective Surgery for Congenital Scoliosis - A Case Report - R. Dalvi, Sairani; Ramdurgkar, Rama; R. Desai, Prapti; Kurdekar, Raghavendra (Journal of Neonatal Surgery, 2025)
A 13-year-old girl presented with progressive thoracolumbar scoliosis, first noticed at birth. Despite no neurological deficits or gait issues, she experienced intermittent pain and visible postural changes. Examination showed a thoracic hump, muscle spasms, rib crowding, and restricted trunk mobility. She underwent corrective spinal surgery, followed by structured physiotherapy. Early physiotherapy significantly improved recovery, mobility, muscle balance, and overall quality of life